Anxiety, Depression and School Absenteeism in Youth With Chronic or Episodic Headache - Céline Rousseau-Salvador; Rémy Amouroux; Daniel Annequin; Alexandre Salvador; Barbara Tourniaire; Stéphane Rusinek (Pain Research and Management)
BACKGROUND: Chronic daily headache (CDH) in children has been documented in general and clinical populations. Comorbid psychological conditions, risk factors and functional outcomes of CDH in children are not well understood.